Relationships between Ghrelin and Obestatin with MDA, Proinflammatory Cytokines, GSH/GSSG Ratio, Catalase Activity, and Semen Parameters in Infertile Patients with Leukocytospermia and Varicocele. (21st October 2019) - Micheli, Lucia; Collodel, Giulia; Cerretani, Daniela; Menchiari, Andrea; Noto, Daria; Signorini, Cinzia; Moretti, Elena
Abstract : Ghrelin and obestatin are involved in many biological functions including reproduction. Growing evidences suggest that both peptides could exert protective and antioxidant activities. In this study, the relationships between ghrelin/obestatin, interleukin-6 (IL-6), tumor necrosis factor- α (TNF- α ), malondialdehyde (MDA), reduced glutathione (GSH), oxidized glutathione (GSSG), expressed as the GSH/GSSG ratio, catalase (CAT), and semen parameters in infertile patients with varicocele or leukocytospermia and controls were investigated. Fifty-six infertile patients (32 with leukocytospermia and 24 with varicocele) and 14 controls participated in this study. Semen analysis was performed following the WHO guidelines. Apoptotic and necrotic sperm were scored by annexin V/propidium iodide assay. Seminal plasma samples were used for the following determinations: ghrelin, obestatin, IL-6, and TNF- α were measured by an immunological method, GSH/GSSG by an enzymatic method, and CAT by spectrophotometric determination. With respect to controls, both the leukocytospermia and varicocele groups showed altered sperm parameters, significantly increased sperm apoptosis (P = 0.009 and P = 0.011, respectively), IL-6 (P = 0.0001 and P = 0.004, respectively), and TNF- α levels (P = 0.0001 and P = 0.002, respectively); both groups had significantly decreased levels of ghrelin P = 0.0001, obestatin (P = 0.0001 and P = 0.006, respectively), and GSH/GSSG ratio (P = 0.003 and P = 0.0001, respectively). The MDA concentration was significantly increased in the leukocytospermia group vs. controls P = 0.0001, in the varicocele group vs. controls P = 0.011, and in the leukocytospermia group vs. the varicocele group P = 0.008 . CAT activity was augmented in both the leukocytospermia and varicocele groups P = 0.0001 vs. controls. The results indicate that both ghrelin and obestatin may play a protective role in human semen and this effect is probably due to their antioxidant properties.